Economic complexity and basic sanitation: an econometric investigation regarding water and sewage services in Brazilian municipalities - Lima, Pedro Augusto Bertucci [UNESP]; Paião, Gilberto Dias [UNESP]; dos Santos, Thalita Lacerda [UNESP]; Furlan, Marcelo; Ferraz, Diogo [UNESP] (Inderscience Publishers, 2023)
Economic complexity investigates the influence of production sophistication on economic growth, human development, and sustainability. However, scarce attention has been done to the influence of complexity on the quality and treatment of sanitary issues, especially in developing regions. For this reason, this article aims to analyse the influence of the Economic Complexity Index on the water and sewage services in Brazilian municipalities. This article used an econometric model with panel data, focusing on four aspects related to water and sewage: water coverage, water quality, sewage coverage, and sewage treatment. The results indicate that regions with a more sophisticated productive structure present better water and sewage coverage levels. However, a sophisticated productive structure did not corroborate to a better water quality nor sewage treatment. This study corroborates with policymakers revealing that the productive structure provides water and sewage access, but it is not adequate in providing water quality and sewage treatment.